The Influence of Akidah Akhlak Learning and Digital Literacy on Students’ Anti-Cyberbullying Behavior - Sopidi, Sopidi; Ilman NZ, Zidni; Bahrul Hayat, Ahmad; Mujadid, Muhamad; Sapari, Sapari (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Cyberbullying has emerged as a critical issue among adolescents, necessitating effective educational interventions. This study aims to analyze the effect of integrating Akidah Akhlak learning and digital literacy on students’ anti-cyberbullying behavior. The study employed a positivist quantitative approach using a quasi-experimental method with a Non-equivalent Control Group Design, as it utilized existing classes without random assignment of participants. The research was conducted at MTs NU Putra 2 Buntet Pesantren Cirebon and involved 47 students, consisting of 23 seventh-grade students as the experimental group and 24 eighth-grade students as the control group. The sampling technique applied was purposive sampling as well as total sampling, since the entire accessible population was included in the study. Data were collected using standardized and validated questionnaires to measure students’ attitudes and behaviors related to cyberbullying. Data analysis was conducted using descriptive and inferential statistics with the assistance of SPSS version 26, including normality tests, homogeneity tests, and hypothesis testing using the Independent Sample t-test at a significance level of 5% (p < 0,05). The results revealed a significant difference in post-test scores between the experimental and control groups (Sig. 0,000 < 0,05), with the experimental group achieving a higher mean score (85,50) compared to the control group (72,15). It can be concluded that integrating spiritual values through Akidah Akhlak learning with digital literacy competencies is effective in strengthening students’ anti-cyberbullying behavior; therefore, schools are encouraged to systematically combine moral education with the enhancement of digital literacy.